A comprehensive battery of flow cytometric immunoassays for the in vitro testing of chemical effects in human blood cells - Pierzchalski, Arkadiusz; Zenclussen, Ana C.; Herberth, Gunda (Frontiers in Immunology, 2024)
Background There is a growing need for immunological assays to test toxic and modulatory effects of chemicals. The assays should be easy to use, reproducible and superior to cell line-based assays. We have therefore developed a comprehensive portfolio of assays based on primary human blood cells that are suitable for testing chemical effects. Methods The flow cytometry-based assays were designed to target a wide range of human peripheral blood mononuclear cells and whole blood, including T cells, NK cells, B cells, basophils and innate-like T cells such as γδT, MAIT and NKT cells. We have selected a set of activation markers for each immune cell, e.g: CD154 (T cells), CD137, CD107a (NK cells), CD63 (basophils), CD69, CD83 (B cells), CD69, IFN-γ (MAIT cells) and we selected cell specific stimuli: aCD3 antibodies (T cells); E. coli and cytokines IL-12/15/18 (MAIT cells); CpG ODN2006, R848 or aCD40 antibodies (B cells), fMLP or aFcϵR1 (basophils) or K562 cells (NK cells). Results By selecting immune cell-specific markers and cell-specific stimuli, we were able to induce particular immune responses from the targeted immune cells. For example, the response to stimulation with anti-CD3 antibodies was in 36.8% of CD107a+CD8+ cells. Cytokine stimulation induced the production of IFN-γ in 30% of MAIT cells. After stimulation with E. coli, around 50% of MAIT cells produced TNF. About 40% of basophils responded to aFcƐR1 stimulation. Similar activation ranges were achieved in K562-stimulated NK cells. Conclusion Our test portfolio covers the most relevant immune cells present in human blood, providing a solid basis for in vitro toxicity and immunomodulatory testing of chemicals. By using human blood, the natural composition of cells found in the blood can be determined and the effects of chemicals can be detected at the cellular level.